Factors influencing online purchase intention of smartphones: A hierarchical regression analysis - Rex P. Bringula; Shirley D. Moraga; Annaliza E. Catacutan; Marilou N. Jamis; Dionito F. Mangao (Cogent Business & Management, 2018)
This study determined which of the factors—company, personal, and technical—could influence online purchase intention of smartphones. Toward this goal, data gathered from 230 students were analyzed using hierarchical regression analysis. Three steps of hierarchical regression analysis disclosed that security and trust were the consistent predictors of online purchase intention of smartphones. Trust was the strongest predictor of online purchase intention of smartphones. It was disclosed that price was initially considered when buying the device. However, subsequent analyses revealed that this variable was no longer considered when personal-related factors were included in the analysis. Quality was not a significant predictor all throughout the analysis. The results of the study offered explanations on the conflicting results of previous studies in terms of price and quality. It was concluded that the study was able to determine the factors that could influence purchase of smartphones in an online environment. Recommendations and implications to theory and practice were also discussed.
Keywords: 650